NEUROLAW: SEVERAL FUNDAMENTAL INSIGHTS INTO JUDICIAL DECISION-MAKING - Valančienė, Dovilė (Teisė, 2017)
The article conceptually reviews the interdisciplinary dialogue between neuroscience and law, examines several fundamental insights of neuroscience on decision-making and judicial decision-making, and seeks to answer the question how the judicial decision-making process can be improved.